2014
DOI: 10.1103/physrevc.90.024304
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy dipole strength inSn112,120

Abstract: The 112,120 Sn(γ, γ ) reactions below the neutron separation energies have been studied at the superconducting Darmstadt electron linear accelerator S-DALINAC for different endpoint energies of the incident bremsstrahlung spectrum. Dipole strength distributions are extracted for 112 Sn up to 9.5 MeV and for 120 Sn up to 9.1 MeV. A concentration of dipole excitations is observed between 5 and 8 MeV in both nuclei. Missing strength due to unobserved decays to excited states is estimated in a statistical model. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 111 publications
4
65
1
Order By: Relevance
“…Instead of using discrete spectroscopic tools, a broad range of techniques has been developed to extract statistical properties, below or in the vicinity of S n , such as the nuclear level density (NLD) and γ-ray strength function (γSF) which are measures of the average nuclear response. Some of the commonly used experimental methods include (i) (γ,γ') scattering using mono-energetic beams [1,2] or Bremsstrahlung photon sources [3,4], (ii) (n, γ) measurements with thermal/cold neutron beams [5,6], average resonance capture [7], (iii) two-step cascade methods using thermal neutrons [8] or charged particle reactions [9], and (iv) isoscalar sensitive techniques [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using discrete spectroscopic tools, a broad range of techniques has been developed to extract statistical properties, below or in the vicinity of S n , such as the nuclear level density (NLD) and γ-ray strength function (γSF) which are measures of the average nuclear response. Some of the commonly used experimental methods include (i) (γ,γ') scattering using mono-energetic beams [1,2] or Bremsstrahlung photon sources [3,4], (ii) (n, γ) measurements with thermal/cold neutron beams [5,6], average resonance capture [7], (iii) two-step cascade methods using thermal neutrons [8] or charged particle reactions [9], and (iv) isoscalar sensitive techniques [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In stable nuclei, dense discrete spectra of dipole states were detected in (γ, γ ) [3][4][5][6][7][8][9] and in (α, α γ) experiments [10][11][12]. Moreover, fairly complete dipole spectra below and above the neutron decay threshold were produced with great accuracy through inelastic proton scattering experiments [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…The theoretical results have been used successfully to analyse the data of different experiments, e.g. [6,[8][9][10][11]13]. Although in many cases the overall features are already reasonably obtained by singlephonon QRPA calculations, multi-phonon effects are indispensable for a proper description of the fragmentation pattern and the total strength of pygmy modes [5].…”
Section: New Modes Of Excitation In Charge-asymmetric Nucleimentioning
confidence: 97%
“…In recent years nuclear density functional theory and nuclear many-body methods -ranging from HFB and (Q)RPA theory to the QPM approach of Soloviev et al -have been used to study systematically ground state properties and multipole response functions of exotic nuclei, especially in the region of the N = 82 and the Z = 50 shell closures, see e.g. [1] and detailed studies are found in [2][3][4][5][6][7][8][9][10][11][12][13][14]. None of those systems can be explored without an adequate reaction theory.…”
Section: Introductionmentioning
confidence: 99%